Inoculum Sources, Infection Periods, and Effects of Environmental Factors on Alternaria Brown Spot of Mandarin in Mediterranean Climate Conditions - Bassimba, Daniel; Mira, José L.; Vicent, Antonio (2017)
Alternaria brown spot (ABS), caused by Alternaria alternata, is a serious disease affecting mandarin in humid and in semi-arid regions. The information available from Florida cannot be easily extrapolated to Mediterranean regions; thus, epidemiological studies were conducted during two consecutive years in Spain. Pathogenic isolates were found in the canopy and leaf litter and on weeds of the genus Sonchus. The pathogen survived in fallen immature leaves for up to 76 days, until complete leaf decay. Conidia of Alternaria spp. were captured continuously and pathogenic isolates were detected in all sampling dates. However, the number of pathogenic isolates was not correlated with the total captured, indicating that morphological identification is not sufficient for airborne inoculum monitoring. In contrast to humid areas, infections occurred mainly in spring and autumn. Classification tree analysis indicated that virtually all infections occurred on weeks with rainfall ≥2.5 mm and average temperature ≥12.5°C. Based on regression quantiles, the amount of rainfall, number of rain days, and total wetness duration were considered important factors increasing ABS incidence during infection periods. The development of decision support systems for ABS control in Mediterranean conditions may benefit from the restricted periods of infection and the strong influence of weather factors in disease onset.